An Association between Anti-Phospholipid Antibodies and Connective Tissue Diseases - Ketha Ravindra Reddy; V.S. Sai Lakshmi (Asian Journal of Medical Research, 2019)
Background: Anti-phospholipid antibodies (APLA) are mostly directed against phospholipids and also with their binding proteins. They are frequently associated with connective tissue disorders. Systemic Lupus Erythematosus (SLE) associated with APLA might cause diagnostic dilemma due to several manifestations mainly neurological, serositis proteinuria, thrombocytopenia, haemolytic anemia, ulceration of legs, which occur in both the conditions. So, we had conducted a study to determine the association between anti-phospholipid antibodies and connective tissue diseases and also compared clinical and laboratory parameters between anti-phospholipid antibody positive and anti-phospholipid antibody negative groups. Subjects and Methods: The present study was conducted among two hundred and four patients who were diagnosed with connective tissue diseases. APLA testing was done at baseline and the patients who were found to be positive for the test, a repeat of the test was performed after 12 weeks. Results: Among the patients with connective tissue diseases (14 p.c) had a positive test result for anti-phoshpolipid antibodies. In the SLE group positive anti-phospholipid antibody was detected among 73.3 p.c of patients, mixed connective tissue disease (MCTD) was present among 13.3 p.c of the patients and systemic sclerosis was present among 13.3 p.c of the patients. Conclusion: Always an anti-phospholipid antibody test should be conducted among all the patients with connective tissue disease for early diagnosis and prevention of life-threatening complications.